A decline in depression treatment following FDA antidepressant warnings largely explains racial/ethnic disparities in prescription fills. Issue 12 (29th September 2017) - Carson, Nicholas J.; Progovac, Ana M.; Wang, Ye; Cook, Benjamin L.
Abstract : Background: The Food and Drug Administration's 2004 antidepressant warning was followed by decreases in antidepressant prescribing for youth. This was due to declines in all types of depression treatment, not just the intended changes in antidepressant prescribing patterns. Little is known about how these patterns varied by race/ethnicity. Method: Data are Medicaid claims from four U.S. states (2002–2009) for youth ages 5–17. Interrupted time series analyses measured changes due to the warning in levels and trends, by race/ethnicity, of three outcomes: antidepressant prescription fills, depression treatment visits, and incident fluoxetine prescription fills. Results: Prewarning, antidepressant fills were increasing across all racial/ethnic groups, fastest for White youth. Postwarning, there was an immediate drop and continued decline in the rate of fills among White youth, more than double the decline in the rate among Black and Latino youth. Prewarning, depression treatment visits were increasing for White and Latino youth. Postwarning, depression treatment stabilized among Latinos, but declined among White youth. Prewarning, incident fluoxetine fills were increasing for all groups. Postwarning, immediate increases and increasing trends of fluoxetine fills were identified for all groups. Conclusions: Antidepressant prescription fills declined most postwarning for White youth, suggesting that risk information may have diffused less rapidly to prescribers or caregivers of minorities. Decreases in depression treatment visits help to explain the declines in antidepressant prescribing and were largest for White youth. An increase in incident fluoxetine fills, the only medication indicated for pediatric depression at the time, suggests that the warning may have shifted prescribing practices.